What conclusion can you draw about vector b if vector a + vector b =vector a - vector b
Answers
Answered by
2
┏_________∞◆∞_________┓
✭✮ӇЄƦЄ ƖƧ ƳƠƲƦ ƛƝƧƜЄƦ✮✭
┗_________∞◆∞_________┛
Given that,
A + B = A - B
We know that,
A + B = √(A² + B² + 2ABcosФ)
A - B = √(A² + B² - 2ABcosФ)
Hence,
√(A² + B² + 2ABcosФ) = √(A² + B² - 2ABcosФ)
A² + B² + 2ABcosФ = A² + B² - 2ABcosФ
4ABcosФ = 0
cosФ = 0
Ф = 90°
Similar questions
Social Sciences,
5 months ago
English,
5 months ago
Math,
5 months ago
English,
11 months ago
Math,
11 months ago